2016
DOI: 10.4315/0362-028x.jfp-15-319
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Quantitative PCR Assays for the Detection and Quantification of the Six Major Non-O157 Escherichia coli Serogroups in Cattle Feces

Abstract: Shiga toxin-producing Escherichia coli (STEC) serogroups O26, O45, O103, O111, O121, and O145, called non-O157 STEC, are important foodborne pathogens. Cattle, a major reservoir, harbor the organisms in the hindgut and shed them in the feces. Although limited data exist on fecal shedding, concentrations of non-O157 STEC in feces have not been reported. The objectives of our study were (i) to develop and validate two multiplex quantitative PCR (mqPCR) assays, targeting O-antigen genes of O26, O103, and O111 (mq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Detecting STEC strains in the feces of cattle, the source of many of these infections, is challenging; however, researchers have begun identifying non-O157 strains using qPCR (Shridhar et al, 2016). In a study comparing culture versus PCR-based methods in detecting non-O157 strains, researchers found that each method detected one or more serogroups that the other method found negative, concluding that both methods are required for accurate detection (Noll et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detecting STEC strains in the feces of cattle, the source of many of these infections, is challenging; however, researchers have begun identifying non-O157 strains using qPCR (Shridhar et al, 2016). In a study comparing culture versus PCR-based methods in detecting non-O157 strains, researchers found that each method detected one or more serogroups that the other method found negative, concluding that both methods are required for accurate detection (Noll et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The reservoirs and vehicles of transmission of non-O157 E. coli strains resemble those seen for O157 strains. Cattle, goats, and sheep, which harbor the pathogen in their hindguts and shed them in feces (Shridhar et al, 2016), have been shown to be important reservoirs for non-O157 as well as O157 STEC. Researchers examining naturally infected beef cows and steer calves found that non-O157 STEC shedding is highest in younger animals at the stage of post-weaning and before entry into the feedlot (Ekiri et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Because Stx is highly potent, the presence of stx genes is tested routinely for distinguishing the virulent strains from commensal strains for epidemiological studies, outbreak investigations and food monitoring. E. coli O157 and other STEC strains are detected by microbiological procedures and multiplex PCR [ 10 , 11 , 12 , 13 ]. The process takes a long time, as the cells have to be grown for several hours before testing can be conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Testing of more colonies may give a more accurate concentration value. Although the spiral plate method used here only tested 10 colonies from an agar plate, the benefit of using this approach is that it can test whether multiple genes originate from one organism, unlike current real-time PCR assays (1,7,31). Most suspensions were quantifiable when concentrations were above 10 4 CFU/g.…”
Section: Discussionmentioning
confidence: 99%
“…Concentration has been determined by use of spiral plate methods for STEC O157:H7 (3,28) or real-time PCR assays that quantify total STEC load or specific serogroups of STEC (1,7,22,31). Real-time PCR assays using multiple targets can detect genes contributed by multiple organisms.…”
mentioning
confidence: 99%